Case Study of a Digital Augmented Reality Intervention for Autism in School Classrooms: Associated With Improved Social Communication, Cognition, and Motivation via Educator and Parent Assessment - Sahin, Ned T.; Abdus-Sabur, Rafiq; Keshav, Neha U.; Liu, Runpeng; Salisbury, Joseph P.; Vahabzadeh, Arshya (Frontiers in Education, 2018)
Background: Impairment in social communication is the primary deficit in school-aged children with autism spectrum disorder (ASD). There are efficacious interventions to address social communication deficits, yet their delivery is hampered by the lack of human and time resources. Emerging assistive technologies, such as smartglasses, may be able to help augment the social communication interventions currently provided by human educators and therapists. While emerging research suggests assistive socio-emotional coaching smartglasses can be effective and usable in research settings, they have yet to be studied amidst the complex social, physical, and time-constrained environment of the school classroom. This structured case study reports on the feasibility and efficacy of 16 intervention sessions of the Empowered Brain Face2Face module, a smartglasses-based social communication intervention. Methods: A 13-year-old fully-verbal adolescent male student with a diagnosis of ASD received a total of 16 smartglasses-aided intervention sessions over a two-week period. Interventions occurred twice-daily during school days and were facilitated by school professionals in a middle school in Massachusetts, USA. Outcomes were measured using the Social Responsiveness Scale 2 (SRS-2), a commonly used validated measure of social communication in children with ASD, by the participant’s parent, paraprofessional, and two teachers. Difficulties in usability during the study were recorded through observation notes. Results: The participant completed the three-week study (one pre-intervention week (baseline) and two intervention weeks) without any observations of adverse effects or usability concerns. The parent and three educators completed the SRS-2 for the baseline and intervention weeks, and results demonstrated significant improvement in social communication after the intervention relative to baseline. The parent, special education teacher, and general education teacher noted marked reductions in SRS-2 total T score, with improvement in SRS-2 social communication, social motivation, social cognition, and restricted interests and repetitive behavior subscales. Conclusion: Smartglasses are a novel assistive technology that can help facilitate social communication and behavioral coaching for students with ASD. The use of the Face2Face module by educators over a two-week period was associated with improvements in social communication. This study supports the use of this novel technology to deliver assistive social communication and behavioral coaching in schools.